2018
DOI: 10.1371/journal.pone.0203265
|View full text |Cite
|
Sign up to set email alerts
|

'We pledge to improve the health of our entire community': Improving health worker motivation and performance in Bihar, India through teamwork, recognition, and non-financial incentives

Abstract: BackgroundMotivation is critical to health worker performance and work quality. In Bihar, India, frontline health workers provide essential health services for the state’s poorest citizens. Yet, there is a shortfall of motivated and skilled providers and a lack of coordination between two cadres of frontline health workers and their supervisors. CARE India developed an approach aimed at improving health workers’ performance by shifting work culture and strengthening teamwork and motivation. The intervention—“T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
0
22
1
Order By: Relevance
“…As a result, HCWs lost their motivation to perform their duties because of inadequate resources and mis-aligned structures. Indeed evidence from other systematic reviews and global health studies confirms that the performance, attrition and retention of frontline HCWs are linked to intrinsic and extrinsic motivational factors such as being proud of their contributions to communities, opportunities for skills improvement and self-development, supportive supervision, proper remuneration, and healthy organizational cultures and work environments [48][49][50]. Some recent studies, for example, highlight opportunities to motivate health care providers in terms of performance-based incentives [51,52] and team-based goals and incentives model [50].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, HCWs lost their motivation to perform their duties because of inadequate resources and mis-aligned structures. Indeed evidence from other systematic reviews and global health studies confirms that the performance, attrition and retention of frontline HCWs are linked to intrinsic and extrinsic motivational factors such as being proud of their contributions to communities, opportunities for skills improvement and self-development, supportive supervision, proper remuneration, and healthy organizational cultures and work environments [48][49][50]. Some recent studies, for example, highlight opportunities to motivate health care providers in terms of performance-based incentives [51,52] and team-based goals and incentives model [50].…”
Section: Discussionmentioning
confidence: 99%
“…87 88 A trial of team-based goal setting for CHWs in Bihar in which health workers worked in teams towards collective goals and were rewarded with public recognition and non-financial incentives demonstrated improvements in motivation and performance. 89 Other alternative approaches to supervision such as community supervision (community defines expectations, tracks performance and provides feedback), group supervision (supervisory visits include multiple CHWs, who can work together to find creative solutions to shared problems) and peer supervision are also being tested, 9 90 91 but these remain areas for further research, according to a recent literature and consultative review. 61 Medicine and equipment shortages among CHWs or at facilities and poor quality of care in facilities limit…”
Section: Bmj Global Healthmentioning
confidence: 99%
“…These results suggest that the approach of combining an integrated set of team-based coverage goals and targets, small non-cash incentives for teams who meet targets and other elements to motivate FLWs has promise for improving FLW motivation and performance, and FLW–beneficiary interactions. In alignment with this point, a prior study reported that various markers of intrinsic motivation (eg, empowerment, job satisfaction) were higher among FLWs from the intervention than control areas, as assessed after intervention 20. These types of improvements represent a first step towards improving health behaviours and outcomes but require further prospective, long-term, mixed methods investigations in other contexts.…”
Section: Discussionmentioning
confidence: 82%